2016
DOI: 10.1177/2396987316650597
|View full text |Cite
|
Sign up to set email alerts
|

Doctor’s follow-up after stroke in the south of Sweden: An observational study from the Swedish stroke register (Riksstroke)

Abstract: Introduction: Information on follow-up practices after stroke in clinical routine are sparse. We studied the probability of doctor's follow-up within 90, 120, 180, and 365 days after hospital discharge, and how patient characteristics were associated with the probability of follow-up, in a large unselected stroke cohort. Patients and methods: Data on patients living in southern Sweden, hospitalized with acute ischemic stroke or intracerebral hemorrhage 1 January 2008 to 31 December 2010, were obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…The concept of adherence, will be assessed by combining information from subjective and objective sources. With supplementary information and evaluation of follow-up routines in primary health care, this sub-study constitutes a valuable approach to a challenging and sparsely studied research area where further data are warranted [ 84 , 85 ]. Secondary prevention is important for the prognosis following a stroke, both because the risk of PCI is strongly increased by a subsequent stroke, but also because optimal treatment of vascular risk factors seem to impact neurodegeneration and small vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of adherence, will be assessed by combining information from subjective and objective sources. With supplementary information and evaluation of follow-up routines in primary health care, this sub-study constitutes a valuable approach to a challenging and sparsely studied research area where further data are warranted [ 84 , 85 ]. Secondary prevention is important for the prognosis following a stroke, both because the risk of PCI is strongly increased by a subsequent stroke, but also because optimal treatment of vascular risk factors seem to impact neurodegeneration and small vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, about 85 to 90% of stroke survivors return to their own environment with or without support services [9, 10]. While there are some data that suggest that stroke survivors may utilize greater healthcare services after their stroke [7, 8, 11, 12], studies have not compared this utilization using a control group. Impaired functional health, higher financial income, younger age, emotional distress [8], pre-stroke dependency [7], living arrangement, social circumstances [7] and access to a physician [6] have been associated with the use of healthcare services after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Low GP follow-up compliance after stroke has been found elsewhere with additional associations. Patients with greater age, pre-stroke ADL dependency, and prior stroke were less likely to receive doctor’s follow-up [21], and earlier outpatient follow-up could likely prevent most avoidable readmissions [22]. Another study initially conducting unadjusted analyses found patients discharged home without healthcare more likely to be readmitted, which challenges our findings, but after adjustment in multivariate analyses the associations disappeared to agree with our analyses [35].…”
Section: Discussionmentioning
confidence: 48%
“…However, very few studies use population-based data to compare outcomes related to patients’ use of ambulatory services after discharge. Some focus on specific interventions in randomized trials [18, 19], some are based on small samples [20] and others only study one service type [21]. Patients receiving early follow-up visits by a general practitioner (GP) [22] or home nursing care after discharge could have significantly different readmission and mortality rates than those without such services.…”
Section: Introductionmentioning
confidence: 99%